An Intelligent Transport System in VANET using Diffusion Model Integrated Zone Partitioning System - Mary Jacob (International Journal of Intelligent Systems and Applications in Engineering, 2024)
With the significant rise in the number of vehicles on the road, the Vehicular Ad-Hoc Network (VANET) is turned into one of the most important study areas. Numerous VANET applications are used to enhance traffic flow, vehicle security, emergency alerts to drivers, accident avoidance, and other comfort-related, non-safety application. By adopting smart transport systems, the major goal of these applications is to modernise many operations related to road traffic, vehicles, drivers, passengers, and pedestrians. The goal of this project is to develop an intelligent vehicular transport system that will increase comfort, road safety, and navigation. A data diffusion model is proposed to transmit emergency messages based on critical zone partitioning for intelligent transport system in Vehicular Ad-Hoc Networks (VANETs). This research illustrates the broadcasting technique of the proposed system. To analyze the proposed system performance a Data diffusion model is created. Partitioning the urgent zone and transmitting emergency messages based on priority are discussed. The objective of this research work is to improve the Packet Delivery Ratio, Throughput, Routing Control Overhead, Packet Loss Ratio and Average One-hop Delay metrics. The system model for the proposed Diffusion Model Integrated Zone Partitioning (DMIZP) technique, the experimental result analysis determines the efficiency of the proposed approach.